(untitled) (Journal of Oriental Studies, 2018)
The purpose of this work is to examine the history of ethnic education of Koreans in Kazakhstan and identify the problem of its preservation on the example of the secondary school named after F. Dzerzhinsky. In Kazakhstan, there are practically no ethnic Korean schools, Korean as an optional class is studied in secondary schools №56 and №136 in Almaty. The author of this work wants to pay special attention to the activities of the high school, which is the only school in the country where the Korean language is studied as a native language from 1 to 11 classes. High school named after F. E. Dzerzhinsky is a unique example of the preservation of the Korean language in Kazakhstan and the issue of preservation and development of this school is a priority for the modern generation of Koreans. This paper was prepared with the support of Grant 30RE003 Ref.No.: 10114610 under the Japan Foundation Short-Term Fellowship Program for 2018-2019.